Whole-cell circular dichroism difference spectroscopy reveals an in vivo-specific deca-heme conformation in bacterial surface cytochromes12. Issue 99 (7th November 2018) - Tokunou, Yoshihide; Chinotaikul, Punthira; Hattori, Shingo; Clarke, Thomas A.; Shi, Liang; Hashimoto, Kazuhito; Ishii, Kazuyuki; Okamoto, Akihiro
Abstract : Our novel analytical framework to identify the inter-heme interaction in deca-heme cytochrome protein MtrC in whole cell revealed that the heme alignment in reduced MtrC is distinct from that in purified system. Abstract : We established whole-cell circular dichroism difference spectroscopy to identify the inter-heme interaction in deca-heme cytochrome protein MtrC in whole cell. Our data showed that the heme alignment of reduced MtrC in whole cell is distinct from that in purified one, suggesting the in vivo specific electron transport kinetics.